Chemical Characterization of Phosphogypsum Resulting from the Processof |Manufacturing Phosphorous Acid from Raw Phosphate Rock (Latakia University Journal -Basic Sciences Series, 2023)
Phosphogypsum is an industrial by-product formed during the production of phosphorus acid and fertilizers from raw phosphates. It mainly consists of CaSO4 and contains impurities such as Zn, Cd, Cu, Pb, Cr, Ni, in addition to many rare earth elements such as cerium and lanthanum.The objective of the current research is to study the chemical and elemental content of phosphogypsum, where the results showed that the main component is calcium sulphate at a rate of 68.5%, and the percentage of P2O5 in phosphogypsum was 2.7%. As for the elemental content, the concentrations of La, Ce, Ni, Cr, Pb , Cd, respectively (6.3, 9.8, 3.42, 3.63, 0.33, , 0.52,) ppm, and the reason for its existence is due to its transfer from raw phosphate to phosphogypsum during the process of manufacturing phosphorus acid by the wet method, as for the chemical and elemental content of crude phosphate taken from Khunaifis, which It was determined using XRF technology, AAS atomic absorption technique and UV-VIS spectroscopy, the results of this research showed that the main component of crude phosphate is calcium oxide by 48.75%, while P2O5 has a percentage of 29.06%, and when studying the elemental content of heavy elements in addition to cerium And lanthanium concentrations were La, Ce, Ni, Cr, Pb, Cd respectively (9.2, 13.5, 10, 4.58, 0.46, 7.02) ppm. The ETF values showed a high transmission rate for each of cerium and lanthanium, reaching 72.59 % for cerium and 68.47% for lanthanum. In general, it is noted that the largest percentage of the lanthanides (cerium and lanthanium) moved to the phosphogypsum resulting from the manufacture of phosphoric acid by the wet method, while the higher percentage of P2O5 moved to the formed phosphoric acid.